Analisis Strategi Bauran Pemasaran Berdasarkan Posisi Siklus Hidup Produk Smartphone Samsung di Kota Manado - Stacy V. Mamentu; Johny R. E. Tampi; Danny D. S. Mukuan (JURNAL ADMINISTRASI BISNIS, 2018)
All companies either companies that produce goods or services want to always exist in the market in order to gain market share and of course to make a profit. Like living things undergo a life cycle which is a process from the beginning of living things are born, grow and develop, mature, and then die, so does a product. Therefore, we must plan the right strategy in managing or managing the business that we run. The purpose of this study is to determine the position of Samsung products in Manado City, in accordance with the product life cycle, and Samsung smartphone marketing mix strategy in Manado City based on the position of the product life cycle, and Samsung smartphone marketing mix strategy in Manado City is in accordance with the marketing mix strategy theory based on the product life cycle position. The product life cycle (PLC) graphically describes the sales history of a product or product class since it was first introduced to the market until it was withdrawn from the market (Tjiptono, 2015: 435). This study uses descriptive research with a quantitative approach with the data analysis method used is the Polli and Cook method and uses data collection techniques in the form of interviews and documentation. This study uses two independent variables set to be studied so that information can be obtained, namely the sale of Samsung products in Manado City in 2013-2017 and the marketing mix strategy of Samsung products in Manado City. The results of this study are based on the calculation of the Polli and Cook Method, it can be seen that the amount of the percentage change in sales is 2.11 (X = 2.11) with a growth limit value of 27.96 and a decrease limit value of -26.90. Thus because the number of percentage values of sales changes are between the growth limit value and the limit of decrease value, it can be concluded thatSamsung smartphones in Manado City are at maturity stage (mature). In general, the Samsung smartphone marketing mix strategy in the city of Manado which is run is in accordance with the marketing mix strategy theory based on the product life cycle position at the maturity stage. It is recommended that retaining customers at this time be the main focus for the company and distribution channels to be further expanded to strategic places and for the less profitable to be reduced. Keywords : marketing mix strategy, product life cycle